Development of an Electrophysiological Assay for Kv7 Modulators on IonWorks Barracuda - Wilenkin, Benjamin; Burris, Kevin D; Eastwood, Brian J; Sher, Emanuele; Williams, Andrew C; Priest, Birgit T (Assay and drug development technologies, 2019)
in vivo